Adaptive Cell Outage Compensation in Self-Organizing Networks. - De la Bandera Cascales, Isabel; Muñoz, Pablo; Serrano, Inmaculada; Barco-Moreno, Raquel (IEEE, 2018)
Within Self-Organizing Networks (SON), the Cell Outage Compensation (COC) functionality is one of the most important use cases in Self-Healing in mobile communication networks. The state-of-the-art has proposed different COC techniques, each of them to be indistinctly applied to all cells in outage. Conversely, this paper presents an important improvement of the COC function by adapting different COC strategies to different cell outage situations. With this objective, a novel COC methodology is proposed. When a cell outage occurs in a network, a detailed analysis of the faulty situation is carried out. The result of this analysis allows to classify the degradation produced by the cell outage in the neighboring cells. Depending on this degradation, different COC algorithms should be applied to each affected neighboring cell. In addition, as another contribution, some COC algorithms based on handover parameters modifications have been applied to a cell outage compensation problem. Results have shown that, by adapting the strategy to the outage impact on neighboring cells, the proposed method outperforms classic strategies.
Keywords: Redes de banda ancha; LTE; Self-Healing; Cell Outage Compensation; Self-Organizing Networks (SON); Fuzzy Logic Controller